Young Investigator Award. 10th International Congress on Pediatric Pulmonology - Middleton, Nicos (My University, 2026)
Oral presentation: Low HDL in Childhood is Associated with Adolescent Asthma. (PhD candidate, Main advisor: Middleton, Nicos)
Keywords: Sciences